2011
DOI: 10.1096/fj.11-195461
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of bilirubin‐induced neonatal lethality in a mouse model of Crigler‐Najjar syndrome type I by AAV9‐mediated gene transfer

Abstract: Crigler-Najjar type I (CNI) syndrome is a recessively inherited disorder characterized by severe unconjugated hyperbilirubinemia caused by uridine diphosphoglucuronosyltransferase 1A1 (UGT1A1) deficiency. The disease is lethal due to bilirubin-induced neurological damage unless phototherapy is applied from birth. However, treatment becomes less effective during growth, and liver transplantation is required. To investigate the pathophysiology of the disease and therapeutic approaches in mice, we generated a mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
157
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(168 citation statements)
references
References 37 publications
11
157
0
Order By: Relevance
“…Ugt1 mutant mice have been described previously (Bortolussi et al, 2012). WT littermates were used as a control.…”
Section: Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ugt1 mutant mice have been described previously (Bortolussi et al, 2012). WT littermates were used as a control.…”
Section: Animalsmentioning
confidence: 99%
“…In the latter case, involving AAV vectors, efficacy was more evident (approximately 50% reduction compared with untreated controls) and long lasting (Bortolussi et al, 2012;Pastore et al, 2012). We have recently shown that neonatal gene transfer of AAV9-CMV-hUGT1A1 to the skeletal muscle can rescue bilirubin-induced lethality in a lethal murine model of CNSI we developed (Bortolussi et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations